Development of an integrated learning device Wordwall application: An elementary school student's science literacy skills - Sugiharti, Asih; Buchori, Achmad; Sulianto, Joko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
The low skills of science teachers, who often lack adequate education levels, mastery of the subject matter, and effective teaching techniques, negatively impact literacy. Therefore, this study aims to develop an integrated learning tool for Wordwall applications to enhance students' scientific literacy skills, ensuring validity, practicality, and effectiveness. This study employed a research and development approach with a four-dimensional (4D) model design. We conducted this research at Public Elementary School 02 Wonokerso. The data collection instruments used were validity sheets, student worksheets, teacher and student response questionnaires, and assessment questions. The study's findings indicated that the learning tools met valid criteria, with the module assessment, student worksheet, and assessment question scores being 82.41, 84.09, and 84.17, respectively. Practicality tests from student and teacher questionnaires meet practical criteria (92.52 and 93.75), respectively. The learning tools are helpful because the